Estranging the loop - Fredric Jameson (Finance and Society, 2020)
Loops make a fitful, but not insignificant appearance in Amin Samman's History in Financial Times. Are we locked into the category of causality by human nature, or would it be possible to invent a new one to give conceptuality to what, in the form of the loop, seems for the moment to be mere figural malaise?
Keywords: 300